Cumulative effects of an herbivorous ecosystem engineer in a heterogeneous landscape. Issue 3 (30th March 2016) - Parsons, Mitchell A.; Barkley, Tela C.; Rachlow, Janet L.; Johnson‐Maynard, Jodi L.; Johnson, Timothy R.; Milling, Charlotte R.; Hammel, John E.; Leslie, Ian
Abstract: Foraging by herbivores alters individual plants and vegetation communities directly, and engineering behaviors such as bioturbation (digging and turning soil) and biodeposition (deposition of feces and urine) can affect soils and physical properties that indirectly influence vegetation and other organisms. Patchy environments often concentrate the activities of animals, potentially increasing the magnitude of their impacts on the vegetative community over time. To evaluate the potential for herbivorous engineers to enhance existing heterogeneity, we quantified the direct and indirect effects of a burrowing herbivore, the pygmy rabbit ( Brachylagus idahoensis ), on soil and vegetation in the sagebrush steppe ecosystem of the western United States, and we evaluated whether the effects were related to duration of occupancy by rabbits. Mounded microtopography (i.e., mima mounds) creates distinct resource islands with relatively tall and dense sagebrush shrubs where pygmy rabbits concentrate burrowing and foraging activities. We quantified soil and vegetation characteristics on mima mounds occupied by rabbits for 1–12 yr and on unoccupied mounds. We expected that browsing would negatively influence slow growing sagebrush shrubs, but that digging and biodeposition would enhance soil nutrients and water infiltration. In addition, we hypothesized that the net effect on sagebrush reproduction would be positive because indirect effects on soil would enhance seed production by mature sagebrush and seedling growth, and because bioturbation would increase seed retention and germination. Pygmy rabbit occupancy had significant cumulative effects on both soil and vegetation properties on occupied mima mounds. Over time, browsing reduced sagebrush canopy cover and percent of individual shrubs that were alive. Soil properties were less influenced by the duration of occupancy of mima mounds than by the localized spatial influence of burrowing; elevated nitrogen levels were associated with burrow entrances. Two measures of sagebrush reproduction (seedling recruitment and inflorescence biomass) increased with duration of burrow occupancy, suggesting that over longer time frames pygmy rabbits enhanced reproduction and recruitment of sagebrush shrubs. Our data demonstrate multiple pathways by which an herbivorous engineer can influence habitat heterogeneity, and they suggest that although pygmy rabbits are inconspicuous on the landscape, the species might play an important role in maintaining and augmenting heterogeneity in the sagebrush steppe.